Comparison of Slow and Forced Vital Capacity on Ability to Evaluate Respiratory Function in Bulbar-Involved Amyotrophic Lateral Sclerosis - Huang, Xin; Du, Chenfang; Yang, Qiong; Fan, Dongsheng (Frontiers in Neurology, 2022)
Background and Objective: The percent predicted forced vital capacity (FVC%) in the pulmonary function test (PFT) is generally used to evaluate respiratory function in amyotrophic lateral sclerosis (ALS). Slow vital capacity (SVC) is another method to evaluate respiratory function. Some neurologists found that FVC% was not reflective of respiratory symptoms and percent predicted SVC (SVC%) were found to be higher in some patients with bulbar-onset ALS. We aimed to compare percent predicted SVC (SVC%) with FVC% in evaluating respiratory function and investigate the associations between the difference in clinical characteristics and the difference between SVC% and FVC% (SVC%-FVC%) in patients with bulbar-involved ALS. Method: This prospective study included bulbar-involved ALS patients who visited Peking University Third Hospital between October 2020 and November 2021. They underwent comprehensive clinical assessments, including bulbar symptom assessments, revised ALS functional rating scale (ALSFRS-R), Rasch-Built Overall Amyotrophic Lateral Sclerosis Disability Scale (Roads) and PFTs. Group differences were analyzed by parametric and nonparametric tests. Results: A total of 59 participants were initially enrolled, and 51 of them were included in the final analysis. In patients with bulbar-involved ALS, SVC% (73.82%±21.95%) was significantly higher (p=0.013) than FVC% (71.42%±23.15%). After controlling for other relevant variables, partial correlation analysis showed a significant correlation (r=-0.352, p=0.041) between ALSFRS-R1 scores and SVC%-FVC%. Conclusion: Our prospective study found that SVC% was significantly higher and more reflective of actual respiratory function than FVC% in patients with bulbar-involved ALS. Furthermore, the severity of dysarthria was found to be positively correlated with SVC%-FVC%, providing a clinical marker for predicting SVC%-FVC%.